YOUNG PEOPLE ARE OUR GREAT FUTURE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, in the last years of independence, the youth policy is reflected in the reforms implemented in the youth activities, in the adopted political decisions. The importance of educating school-aged students in the spirit of patriotism, specific general laws of social society, normative procedures related to youth activities are revealed.